PENERAPAN ALGORITMA C4.5 UNTUK PENGUKURAN TINGKAT KEPUASAN SISWA TEHADAP KINERJA GURU - Muhammad Basyier Ardima; Bilqis, Shona Chay; Idris, Mochamad (Program Studi Informatika Medis Universitas Muhammadiyah Muara Bungo, 2024)
ABSTRACT This research aims to determine the level of student satisfaction with teacher performance at MA Miftahussalam Demak by applying the C4.5 algorithm. By knowing the level of student satisfaction, the school can improve services in terms of teaching if they are not good and further improve services if the level of satisfaction is good. The method used in this research uses data mining techniques, classification methods with the C.45 algorithm, where the data source used is a questionnaire involving 3 sample classes, namely 1 class X, 1 class XI, and 1 class XII from the total number of MA students. Miftahussalam Demak. The attributes used as parameters for assessing student satisfaction include: mastery of the material, explanation of the material, time discipline, concern, and communication. The benefit of this research is to improve the quality of teacher performance and improve the quality of teacher teaching. Of the 118 data, 104 students could be classified as satisfied and 14 students as dissatisfied with the teacher's performance with an accuracy of 96.6%.